Karakteristik Morfoekotipe Pohon Induk Pala Sukabumi sebagai Sumber Benih - Handi Supriadi; Ilham Nur Adhi Wicaksono (Jurnal Tanaman Industri dan Penyegar, 2011)
Nutmeg farm in Sukabumi has a high economic value and play important role in increasing farmers' income. To develop the nutmeg farm in this area need source of superior seed from the selected parent, then the result will be optimal. Study of parent performance and  proximate content of  nutmeg using survey method conducted in October 2010. Parent of nutmeg in Sukabumi has a pyramidal shape of canopy. Canopy width of 10.63 m (east-west) and 10.72 m (north-south), obovat leaf shape, round shape fruit with fresh weight of 78.31 g, red color of mace covering 87. 10% of seed and fresh weight of 2.33 g/grain. Fruit production is quite high, reaching 5.343 fruit/ crop/year. The content of proximate (volatile oil content and myristicin) of fruit was quite high, especially at a young age (3-6 months). Sukabumi categorized as very wet climates area (type A), and relatively less fertile land with sandy loam texture.